Main reproductive diseases that affect cows after calving in the State of Rondônia (Research, Society and Development, 2025)
This article aims to describe the main reproductive diseases that affect cows in the postpartum period, highlighting metritis, placenta retention, and metabolic disorders, such as ketosis and abomasa displacement. The study was carried out through a literature review. The negative impact of these diseases on milk productivity and the reproductive efficiency of herds was verified, compromising the sustainability of rural properties. The implementation of preventive measures and early diagnosis is essential to minimize these impacts. The results obtained in this review indicate that correct management of the puerperium can significantly improve conception rates and reduce associated economic losses. Prevention and early diagnosis are essential to maintaining the reproductive health of animals and ensuring good results in livestock activity.